Strategi Pembentukan Sosial Emosional Anak Melalui Sinergi Peran Orang Tua Dan Guru Di Era Digital - Dewi Fatimah; Akhmad Iqbal (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The rapid advancement of digital technology has significantly increased gadget use among young children, raising concerns about its potential impact on their social-emotional development. This study aims to examine the effects of gadget use on early childhood social-emotional development and to explore strategies for fostering these competencies through the collaborative roles of teachers and parents in the digital era. A descriptive qualitative approach with a case study design was employed, involving children aged 4–5 years at SPS Anggur 2, Umbulsari Village, Umbulsari District, Jember Regency, Indonesia. Data were collected through observations, interviews, and documentation, and analyzed using the interactive data analysis model developed by Miles, Huberman, and Saldaña. The findings reveal that excessive gadget use reduces children's social interaction, promotes egocentric behavior, hinders their ability to cooperate with peers, and limits their capacity for emotional regulation. Conversely, the consistent implementation of responsibility, patience, discipline, and cooperation as daily habits by teachers, reinforced through active parental involvement via WhatsApp communication, contributed positively to children's social-emotional development. These findings suggest that effective collaboration between teachers and parents, supported by digital communication, represents a promising strategy for optimizing early childhood social-emotional development in the digital era.